Assistive technology use by disability type and race: exploration of a population-based health survey. (17th February 2016) - Ilunga Tshiswaka, Daudet; Loggins Clay, Shondra; Chiu, Chung-Yi; Alston, Reginald; Lewis, Allen
Abstract: Purpose : To examine the relationships among Assistive Technology (AT) use, race, type of disability and selected other demographic characteristics. Method : Using 2009 National Health Interview Survey, descriptive statistics, statistical interactions and binary logistic regression were performed to identify, contrast and predict the likelihood of using AT based on the type of disability among African Americans (AAs) and European Americans (EAs). Results : We found that more AAs (10% within group proportion of total AAs) used AT compared to EAs (7.5% within group proportion of total EAs). Physical ( p  < 0.001), auditory ( p  = 0.028) and emotional ( p  = 0.008) impairments were statistically significant predictors of AT use. However, physical impairment as a predictor of AT use was greater among AAs (OR = 222.49, CI: 64.04–773.04, p  < 0.001) than EAs (OR = 50.77, CI: 31.78–81.12, p  < 0.001). EAs had a greater number of disabling conditions that predict the use of AT than AAs, whereas AAs had more demographic characteristics beyond race that predict AT use than EAs. Conclusions : Disparities were observed in AT usage by disability types and demographic characteristics between AAs and EAs. Moreover, the predictive strength of AT usage based on disability types and other demographic variables differed by races. Overall, the findings about the different relationships among race, disability type, and AT use are found. Implications for Rehabilitation: The finding may inform the development of initiatives by rehabilitation leaders to encourage the use of AT by AAs and EAs according to their type of impairment. Having identified physical impairment as statistically significant predictor of AT use greater among AAs, rehabilitation leaders should ensure that people living with those types of disability have access to the corresponding type of AT and can use them effectively.